(untitled) (Revista Rupturas, 2017)
Throughout this article we intend to show how different women artists have used their body as a canvas of expression. Their dissident bodies, opened and taken to the extreme, will be subject of representation and self-affirmation, through which you will empower and resist against the considered patriarchal absolute truths, according towomen have been represented as objects of pleasure for the male look.